An IoT Design Effectiveness and Reliability of Electric Power Circuit Breakers - Aryza, Solly; Lubis, Zulkarnain; Putra, Khairil (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
Along with the very rapid development of technology in the current era of globalization. It became3The main instrument in the progress of various social and life aspects. Currently, many people use technology to help solve several problems in life. Almost every activity carried out by humans always uses technology. The use of automated security instruments has become an option nowadays. In modern times like now there are many kinds of technology, and therefore I will develop technology with better security instruments.